2021
DOI: 10.31083/j.jin2002052
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of degradomics as predictors of complications and clinical outcome in aneurysmal subarachnoid hemorrhage

Abstract: Most of the debilitating conditions following aneurysmal subarachnoid hemorrhage result from symptomatic cerebral vasospasm and delayed cerebral ischemia. Several scales are being used, but they still lack objectivity and fail to quantify complications considered essential for prognostication routine use of biomarkers to predict complications and outcomes after aneurysmal rupture is still experimental. Degradomics were studied extensively in traumatic brain injury, but there is no discussion of these biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Result suggests a general role of ubiquitination associated pathways, including ubiquitin protein binding activity and ubiquitin-like protein binding activity, in all 6 studied subtypes. Through literature survey, we found that involvement of ubiquitination relevant pathways in aneurysm pathogenesis has been reported before in ASH, AAA, CA, AA and AD [ 15 21 ]. Thus, it is highly possible that ubiquitination extensively participates in progress of different aneurysmal diseases, through regulation of vascular inflammation and VSMCs phenotypic changes.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Result suggests a general role of ubiquitination associated pathways, including ubiquitin protein binding activity and ubiquitin-like protein binding activity, in all 6 studied subtypes. Through literature survey, we found that involvement of ubiquitination relevant pathways in aneurysm pathogenesis has been reported before in ASH, AAA, CA, AA and AD [ 15 21 ]. Thus, it is highly possible that ubiquitination extensively participates in progress of different aneurysmal diseases, through regulation of vascular inflammation and VSMCs phenotypic changes.…”
Section: Discussionmentioning
confidence: 87%
“…Through literature searches we found that the participant of ubiquitination related proteins (e.g. UCHL1, RNF213, UBR3, ARIH1) in pathogenesis of above-mentioned human aneurysm subtypes (ASH, AAA, CA, AA, AD) has been widely reported before [ 15 21 ]. As we already know, the ubiquitin-proteasome system (UPS) is a critical pathway in eukaryotic cells which functions through degrading cytosolic and nuclear proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Glial fibrillary acidic protein (GFAP) is abundant in astrocytes and is necessary for CNS integrity and maintenance. A recent analysis of clinical reports has suggested that serum GFAP can be a useful tool to assess the clinical outcomes of patients with aneurysmal subarachnoid hemorrhage (SAH) [14]. GFAP is also a substrate of calpain-II protease and a widely used biomarker of astrogliosis in TBI [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, alpha-II-spectrin, a neuronal scaffolding protein, is also a substrate of calpain II [16]. In particular, a recent clinical study reported correlation of alpha-II-spectrin breakdown product (SBDP) level with the clinical outcome and severity in patients with aneurysmal SAH [14]. Accumulation of breakdown products (BDPs) from GFAP and alpha-II-spectrin cleaved by calpain-II has been identified in the cerebrospinal fluid (CSF) after TBI [17].…”
Section: Introductionmentioning
confidence: 99%